THE EFFECT OF CARBON EMISSION DISCLOSURE, ENVIRONMENTAL COSTS, AND GOOD CORPORATE GOVERNANCE ON FIRM VALUE - Nofia Ika Wijayanti; Ardian Widiarto; Mohammad Hasanudin (Applied Accounting and Management Review (AAMAR), 2026)
This study aims to examine and analyze the effect of carbon emission disclosure, environmental costs, and good corporate governance on firm value in basic materials sector companies listed on the Indonesia Stock Exchange during the 2022–2024 period. The research employs a quantitative method using secondary data obtained from companies’ annual reports and sustainability reports. The research sample was selected using a purposive sampling technique, resulting in 28 companies with a total of 84 observations. Data analysis was conducted using multiple linear regression with EViews 12 software. The results indicate that (1) carbon emission disclosure has no significant effect on firm value, (2) environmental costs have no significant effect on firm value, and (3) good corporate governance has a positive and significant effect on firm value.